Diné traditional medicine use and wellbeing among navajo adults during the COVID-19 pandemic: A cross-sectional study - Rachelle L. Begay; Heidi E. Brown; Priscilla R. Sanderson; Robin B. Harris (PLoS ONE, 2025)
Objective To assess perceptions of the impact of the COVID-19 pandemic on access, utilization, and perceived quality of Diné traditional medicine and healing (DTM) and psychosocial wellbeing among members of the Navajo Nation. Methods From May to October 2021, a convenience sample of 153 self-identified Navajo participants were recruited to complete a cross-sectional survey. We developed the survey to gather sociodemographic participant information and explored the perceived impact of the COVID-19 pandemic on Navajo Nation members’ access, utilization, and quality of health care (including DTM practices), employment and finances, and psychosocial wellbeing. Data were analyses using descriptive statistics and Wilcoxon matched-pairs signed-rank test with comparisons made by DTM use. Results We found that nearly half (n = 74, 48.7%) of the study sample reported use of Diné traditional medicine (DTM) or healing during the COVID-19 pandemic. There were no significant differences (P > 0.05) in history of a prior positive COVID-19 test between DTM users and non-users. DTM users indicated that the COVID-19 pandemic had minimal impact on the barriers or issues such as transportation, elder-/childcare or appointment availability they faced in receiving DTM care or healing (P > 0.05 on all pre- vs mid-pandemic scores) and scored higher on the COVID-19 Risk Factor Score than non-users (P = 0.01). Conclusion Despite significant challenges imposed by the COVID-19 pandemic, Diné people were still able to access DTM. Diné traditional medicine and healing is a critical component of overall health and well-being for the Diné people.